RELIGIO-POLITICAL DISCOURSES IN DOCUMENTARY FILMS ON IRAQ PROMOTING PEACE OR CONFLICT - Abida Ashraf (Islamic Communication Journal, 2019)
In the information age, media has become an important tool to seek information for clarity but it is paradoxical. This study shows whether documentaries are projecting skepticism and sarcasm of Iraqi people due to volatile, uncertain complex, and ambiguous (VUCA) conditions or projecting VUCA discourses for the restoration of peace and harmony. The object of this study consists of Oscar-winning and Oscar-nominated documentary films from 2003 to 2011 with a total of 45 films. The year 2003 is selected for its demarcation of U.S.-led invasion of Iraq which started in March 2003 and toppled over the government of Saddam Hussein. The year 2011 denotes the end with the departure of US troops in 2011. Through the criterion sampling, four films are selected that depict Iraq and all the four got nomination for Oscar that include: Iraq in Fragments (2006-Nomination); My Country My Country (2006-N); No End in Sight (2007-N); Operation Homecoming: Writing the Wartime Experience (2007-N). To explore Iraqi people’s perspectives, a further sampling is applied and two documentaries are selected depicting entanglement of religion and politics in Iraq from Iraqi people’s perspective.